2017
DOI: 10.1080/08897077.2015.1048922
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of Risky Drinking: Knowledge of Daily and Weekly Low-Risk Guidelines and Standard Drink Sizes

Abstract: Most patients in primary care don't know specifics of the National Institute on Alcohol Abuse and Alcoholism (NIAAA) guidelines for low-risk drinking. Exploring patient perceptions of low-risk guidelines and current drinking behavior may reveal discrepancies worth discussing. For risky drinkers, most of whom don't know daily and weekly low-risk guidelines or standard drink sizes, education can be vital in intervening. Findings suggest the need for detailed and explicit social marketing and communication on exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Unlike the UK study, however, clinicians in this study rarely cited patients being too frail or unwell as barriers to advice provision, possibly because of generally favourable survival rates among breast cancer patients, who formed the basis of this enquiry, compared to other heterogeneous patient samples (Kaplan, Malmgren, Atwood, & Calip, 2015). The observation that the standard drinks construct is poorly understood by both clinicians and patients supports the results of two other studies which showed primary care patients and doctors of various specialities were generally unable to answer correctly when provided with questionnaires on standard drink volumes (Sprague & Vinson, 2015;Welsh et al, 2014). A lack of knowledge or clarity surrounding public health guidelines may explain why some clinicians were reluctant to provide alcohol advice in their daily practice, or chose to avoid the concept of standard drinks in discussions about alcohol.…”
Section: Discussionsupporting
confidence: 71%
“…Unlike the UK study, however, clinicians in this study rarely cited patients being too frail or unwell as barriers to advice provision, possibly because of generally favourable survival rates among breast cancer patients, who formed the basis of this enquiry, compared to other heterogeneous patient samples (Kaplan, Malmgren, Atwood, & Calip, 2015). The observation that the standard drinks construct is poorly understood by both clinicians and patients supports the results of two other studies which showed primary care patients and doctors of various specialities were generally unable to answer correctly when provided with questionnaires on standard drink volumes (Sprague & Vinson, 2015;Welsh et al, 2014). A lack of knowledge or clarity surrounding public health guidelines may explain why some clinicians were reluctant to provide alcohol advice in their daily practice, or chose to avoid the concept of standard drinks in discussions about alcohol.…”
Section: Discussionsupporting
confidence: 71%
“…Further, people who frequently binge drink have sometimes been shown to have poorer knowledge of the typical definition of binge drinking than people who abstain or drink moderately (Bonar et al., 2012). But in other work, people who binge drink were more likely than people who abstain or drink moderately to know daily and weekly “safe” drinking limits (although note that only 10% of those who binge gave correct definitions) (Sprague & Vinson, 2017). Additionally, even people who are aware of public health guidelines defining low versus high‐risk drinking may be unlikely to refer to this information when they make decisions about their alcohol use (Lovatt et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, relevant AUDIT items are often not adapted to account for differing national standard drink sizes, as required in the AUDIT manual [ 13 , 16 ]. Second, even in countries where the standard drink concept is officially used to standardize the size of retail alcohol, consumers are often not acquainted with the concept and many are unable to convert their consumption correctly [ 17 , 18 ]. For instance, when asked to pour their usual drink and subsequently estimate the number of standard drinks it contained, primary health care patients in the United Kingdom over- or underestimated their actual drink size by at least 0.5 standard drinks in more than half of the cases [ 19 ].…”
Section: Introductionmentioning
confidence: 99%